COMPARATIVE ANALYSES OF THE BANKING ENVIRONMENT IN TRANSITION COUNTRIES - Djalilov, Khurshid; Hölscher, Jens (Economic Annals, 2016)
This paper investigates the dynamics of the banking environment in early and late transition countries for the period 2000-2012. We consider macroeconomic, governance, economic freedom, financial depth, industrial, bankspecific, and CSR variables to compare the banking environment in transition countries. Our analyses show the presence of differences in the banking environment of two groups of transition countries: however, this gap shrunk over the period 2000-2012. The late transition countries have lower scores in the variables ‘Investment’ and ‘Financial freedom’, implying that in the future the governments of these countries may focus on improving the investment and financial climate.